The Collection Of Authors Review Of Literature About Self- Help Groups In India - K.NITHILA,; Dr.V.VEERAMUTHU,; BOSE, Dr.S.SUBASH CHANDRA; KUMAR, Dr. K. SENTHIL (The journal of contemporary issues in business and government, 2021)
The concept of self help groups has been evolved to organize the rural poor to meet their productive and consumption needs out of their saving. A self help group is a small economically homogeneous affinity group of the rural poor voluntarily coming to gather to save small amount regularly. The origin of self-help group can be traced is from Grameen bank of Bangladesh, which was founded by Mohamed Yunus. SGHs were started and formed in 1975. In India NABARD initiated in 1986-1987. The absence of institutional credits available in the rural area has led to the establishment of SHGs. Self- Help Group or in-short SHG is now a well-known concept. It is now almost two decade old. It is reported that the SHGs have a role in hastening country‟s economic development. SHGs have now evolved as a movement. Mainly, members of the SHGs are women. Consequently, participation of women in the country‟s economic development is increasing. They also play an important role in elevating the economic status of their families. This has led boost to the process of women‟s empowerment. so here I presented the collection of authors review of Literature about self-help groups.